Epidemics X Popular Housing in Rio de Janeiro : Analysis through the SWOT Matrix - Costa, Mariana de Melo; Diniz, Luciana Nemer (Electronic Journal "Fórum Ambiental da Alta Paulista", 2021)
The work comparatively analyzes the relation between popular housing and the main epidemics in Rio de Janeiro, from the end of the 19th century to the present day. The text rescues the memory of the tenements (the first popular form of housing), recalling the mortality of Yellow Fever and Spanish Flu; continues to study the formation process of the favelas, in parallel to the Dengue and Covid 19 epidemics, and the solutions implemented by the government with the objective of improve sanitary conditions in the form of housing estates, and more recently, in their urbanization. The SWOT Analysis, a reflection and positioning tool in relation to situations, widely applied in engineering and administration, it was used to list points of weakness and potential solutions in low-income housing in the face of sanitary problems and the solutions brought by the Government. In the methodology, consultations with secondary sources (books, articles, and newspapers) and iconographic research that illustrate the situations and provide support for the application of the SWOT analysis stand out. The conclusions highlight the extent to which epidemics overwhelmingly plague the population living in needy areas, whose absence of wholesome and appropriate urban solutions demonstrate the lack of Urban Planning and Management.